Study on the effect of cellulose loading and ph on water absorbency of superabsorbent polymer composite - Nurhafizah Izzati, Kasim (2014)
Cellulose is natural polymer that can be found abundantly in the earth which has biorenewable and biodegrable abilities. Over the last several decades, the uses of synthetic polymers in all kind of applications and fields make the earth in the state of danger. As known, polymers material is difficult to dispose and can cause to environmental issues. Synthetic polymers wastes are the big problems that contribute to environmental and ecological damage. Therefore, the aim of this research is to increase the water absorbency of superabsorbent polymer by using the natural polymer which is cellulose as filler. It was believed that the incorporation of filler in SAP could increase the water absorbency of the polymer. In this study, the graft polymerization has been chosen to prepare the superabsorbent polymer composite (SAPC). The water absorbency property is observed by varied the filler loading contents and pH values. Based on the results obtained, the optimum of water absorbency of SAPC was shown at 2wt% of cellulose content. This 2wt% of SAPC was then immersed into acid and basic solution at different pH solution and the result shown the optimum water absorbency were observed at 2 wt% of cellulose loading. Meanwhile, the optimum water absorbency at different pH value also can be observed at both solution; acidic (pH 2) and basic (pH 12). For the effect of cellulose loading, the observed result was supported by SEM microstructures of SAPC where the surface morphology of SAPC at 2wt% of filler contents shown coarse, undulant surface and multiple porous. Meanwhile, the microstructure of SAPC at 10wt% show rigid and dense surface. The research objective has been successfully achieved in studying the effect of SAPC towards filler contents and pH values. As result, cellulose-SAPC (2.0 wt%) reveals with multiple porous structure that suitable for penetration of water into polymeric network. Meanwhile pH 2 and pH 12 are the optimum condition for water absorbency due to ionic charge strength from acidic and basic solution. Therefore, this research has proved that the cellulose SAPC was able to enhance the water absorbency of superabsorbent polymer which further could give better contributions in various applications and also more environmental friendly.